2006
DOI: 10.1186/1471-2407-6-171
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein expression in canine malignant mammary tumours

Abstract: Background: Abnormal levels of Heat Shock Proteins (HSPs) have been observed in many human neoplasms including breast cancer and it has been demonstrated that they have both prognostic and therapeutic implications. In this study, we evaluated immunohistochemical expression of HSPs in normal and neoplastic canine mammary glands and confronted these results with overall survival (OS), in order to understand the role of HSPs in carcinogenesis and to establish their potential prognostic and/or therapeutic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 67 publications
2
44
0
2
Order By: Relevance
“…Similar studies are conducted in veterinary medicine, but to a lesser extent (Isomoto et al, 2003). A similar study was conducted by Rommanucci (2005) in mammary gland tumors in female dogs (Romanucci et al, 2006). She found Hsp70 and Hsp90 expression in simple and complex, as well as solid-type adenocarcinomas.…”
Section: Discusionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar studies are conducted in veterinary medicine, but to a lesser extent (Isomoto et al, 2003). A similar study was conducted by Rommanucci (2005) in mammary gland tumors in female dogs (Romanucci et al, 2006). She found Hsp70 and Hsp90 expression in simple and complex, as well as solid-type adenocarcinomas.…”
Section: Discusionsupporting
confidence: 64%
“…Paraffin sections on slides covered with 2% saline solution in acetone, at the temperature of 42 0 C were used for immunohistochemical methods. In immunohistochemical reactions, the following antibodies, properly diluted in 1% BSA (Sigma), were used: mouse monoclonal antibody against human nuclear antigen Ki-67 (Dako) diluted 1:75 (Nieto et al, 2000), mouse monoclonal antibodies against p53 (Dako) human protein, diluted at a ratio 1:25 (Gamblin et al, 1994;Rodo, 2007), mouse monoclonal antibodies against alpha (Dako) human estrogen receptor, diluted at a ratio 1:35 (Mulas et al, 2005), mouse monoclonal antibodies against COX-2 (Dako) human receptor, diluted at a ratio 1:100 (Queiroga et al, 2007;Doré et al, 2003;Soslow et al, 2000), mouse monoclonal antibodies against Hsp70 (Novocastra) human heat shock proteins, diluted at a ratio 1:40 (Romanucci et al, 2006), mouse monoclonal antibodies against Hsp90 (Novocastra) human heat shock proteins, diluted at a ratio 1:40 (Romanucci et al, 2006 ) and mouse monoclonal antibodies against P-glycoprotein (Sigma), diluted at a ratio 1:100 (Petterino et al, 2006). Sections were deparafinized in xylene and rehydrated in increasing concentrations of alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, HSP60 together with their peptides could somehow induce a better response of lymphocytes to CMT. On the other hand, other HSP types, such as HSP27, HSP72 and HSP90 were studied in mammary carcinomas in bitches and presenting results that indicate the association of these proteins with the carcinogenesis process [22]. However, more studies are needed to understand the involvement of HSP60 in CMT.…”
Section: Discussionmentioning
confidence: 99%
“…The heat shock proteins (HSP) are a large family of molecular chaperon proteins [5]. Increased HSP in damaged cells may also aid in cell integrity, since it inhibits the apoptosis [6], and overexpression of the different proteins of this group is related to a poorer prognosis of the patient, including MMT [22].…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, the expression of heat shock proteins was found in squamous cell carcinoma of the skin (Romanucci et al 2005, Bongiovanni et al 2008, cervical cancer (Chu et al 2001) and mammary gland tumors (Kumaraguruparan et al 2006, Romanucci et al 2006. Romanucci (2006) demonstrated the expression of Hsp90 in all examined tumors (simple and complex carcinomas) and found that these proteins are associated with poor outcome and are involved in carcinogenesis in the same way as heat shock protein 27. Available published data (Chen et al 1999) show that in breast cancer cells, the overexpression of heat shock protein 70 is also associated with poor prognosis.…”
Section: Introductionmentioning
confidence: 93%